Lanostane triterpenoids, spiro-astraodoric acid, and astraodoric acids E and F, from the edible mushroom Astraeus odoratus. (September 2017) - Srisurichan, Suphongphan; Piapukiew, Jittra; Puthong, Songchan; Pornpakakul, Surachai
Graphical abstract: Highlights: Three new lanostane-type triterpenoids were isolated. Their structures were established by spectroscopic data. Cytotoxic activities of isolated compounds were tested on six human cancer cell lines. Abstract: Three lanostane-type triterpenoids, spiro-astraodoric acid (1 ), and astraodoric acids E and F (2 and3 ), together with 6 known compounds (4 –9 ) were isolated from fruit bodies of an edible mushroom, Astraeus odoratus . Compound1 possessed an unusual spirocyclic lanostane triterpenoid structure. Their structures were determined by spectroscopic analysis and the absolute configuration of spiro-astraodoric acid and astraodoric acids was described herein. Cytotoxicity of the isolated compounds was tested against six human cancer cell lines.